Description of Mental Emotional Disorders in School-Age Children - Azat Aprianto; Riri Novayelinda; Arneliwati Arneliwati (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Introduction: Mental emotional development that is not good will have several impacts on children, especially in the maturation of their character. This results in emotional mental disorders which can be in the form of high-risk behaviors such as feeling unhappy, having difficulty establishing relationships with other people, and so on. Method. Research using a simple descriptive research design. The population in this study were parents of elementary school children in the Sri Meranti Village area, the number of samples in this study were 210 respondents, taken using an accidental sampling technique. Results. The results obtained from this study indicate that around (80.0%) children experience mental emotional disorders which are in the normal range on the difficulty score, while on the strength score (proportional) it is found that approximately (82.4%) experience mental emotional disorders at normal range. Conclusion. The conclusions obtained in children with mental emotional disorders are in the normal range both in difficulty scores and strength scores (proportional).